Learning vocabulary through meaning-focused input: Replication of Elley (1989) and Liu & Nation (1985). (17th March 2015) - Webb, Stuart
Abstract : There has been a great deal of research on first language (L1) and second language (L2) learning through meaning-focused input since Nagy, Herman & Anderson's (1985 ) seminal study of incidental vocabulary learning through reading. Two strands of research within this area are incidental vocabulary learning through listening and guessing from context. This article discusses widely-cited studies from each of these areas – Elley (1989 ) and Liu & Nation (1985 ) – that deserve to be replicated. Both studies made important contributions to the field, were original in their designs, and advanced our understanding of how vocabulary is learned in context. The benefits of replicating these two studies are described and several suggestions are made for how the replications might be completed.